PERILAKU CYBERLOAFING DITINJAU DARI PSYCHOLOGICAL CAPITAL DAN ADVERSITY QUOTIENT - Devy Sofyanty (Universitas Bina Sarana Informatika, 2019)
Abstract- Cyberloafing is the behavior of employees who use corporate or private internet for purposes that have nothing to do with work and are carried out during office hours. Assessing cyberloafing behavior in companies, institutions or organizations is important to minimize or even eliminate the factors that cause cyberloafing behavior. This study aims to examine and analyze empirically the influence of psychological capital and adversity quotient on cyberloafing behavior. The research method uses quantitative methods while the data collection technique is done through interviews and questionnaires, while the sampling technique used in this study uses purposive sampling technique. The subjects in this study were 150 employees in the Ministry of Energy and Mineral Resources of the Republic of Indonesia. Data were analyzed using multiple linear regression. Based on the results of the analysis, the following findings were obtained: (1) simultaneously psychological capital and adversity quotient negative and significant impact on cyberloafing behavior, (2) partially psychological capital negative and significant impact on cyberloafing behavior, (3) partially adversity quotient negative and significant impact on cyberloafing behavior. Keywords: Psychological Capital, Adversity Quotient, Cyberloafing Behavior